2014
DOI: 10.1128/jvi.02735-13
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage mv4 Site-Specific Recombination: the Central Role of the P2 mv4 Int-Binding Site

Abstract: bThe contributions of the five mv4 Int-and two mv4 Xis arm-binding sites to the spatial intasome organization of bacteriophage mv4 were found not to be equivalent. The 8-bp overlap region was mapped to the left extremity of the core region and is directly flanked by the P2 Int arm-binding site. These results and the absence of characteristic Int core-binding sites suggest that the P2 site is the determinant for integrase positioning and recognition of the core region. During the establishment of the lysogeny, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 15 publications
0
18
2
Order By: Relevance
“…Interestingly, when considering the consensus sequences rather than the WT sequences, the DNA motifs surrounding the overlap region exhibited complementarity, with purines enrichment at the left-side and pyrimidines at the right-side. Thus, in contrast to the previous study that concluded there might be an arm-type site adjacent to the overlap region (42), our analysis strongly supports the classical organization of heterobivalent YR recombination systems for the 21-bp attB and core-attP sites, with imperfect inverted-repeated patterns flanking each strand-exchange region (Figure 4C), and defining BOB' and COC' structures for attB and core-attP respectively, in accordance with the phage lambda terminology.…”
Section: Attb and Core-attp Organisations Are Similar To Classical Yr...contrasting
confidence: 96%
See 4 more Smart Citations
“…Interestingly, when considering the consensus sequences rather than the WT sequences, the DNA motifs surrounding the overlap region exhibited complementarity, with purines enrichment at the left-side and pyrimidines at the right-side. Thus, in contrast to the previous study that concluded there might be an arm-type site adjacent to the overlap region (42), our analysis strongly supports the classical organization of heterobivalent YR recombination systems for the 21-bp attB and core-attP sites, with imperfect inverted-repeated patterns flanking each strand-exchange region (Figure 4C), and defining BOB' and COC' structures for attB and core-attP respectively, in accordance with the phage lambda terminology.…”
Section: Attb and Core-attp Organisations Are Similar To Classical Yr...contrasting
confidence: 96%
“…Given the organisational peculiarities of the mv4 attP core-region and attB site (40, 42), both sites underwent a comprehensive experimental reevaluation using a random DNA libraries based approach (59), with the rational that DNA positions encompassing these core regions should display constraints in nucleotide composition. Those DNA libraries, corresponding either to the attB site or to the core-region of the attP site, harboured a range of 7 to 10 randomized positions (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations